Gestion de mantenimiento del área de laminados en la empresa Adelca mediante el programa SAP (PM). - Jácome Changoluisa, Luis Alexander (2023)
The Aceria del Ecuador C.A factory aims to keep its facilities and industrial processes on par with the development of new technologies, this research proposed a maintenance management with the help of SAP PM software for the maintenance management of industrial plants. The maintenance management will focus fully on the rolling mill T07, the maintenance mangagement will generate a maintenance plan for the critical equipment of the supported rolling mill production line of an AMEF matrix and criticality analysis of equipment, with the application of surveys allow us to know about the different equipment that is made up of the rolling mill T07; through the criticality analysis it was possible to classify the equipment between critical, important and essential, to work specifically with the critical ones, the maintenance plan was developed in order to be able to execute it in the SAP PM program, therefore it is concluded that the maintenance management carried out contributed to the reduction of failures in critical equipment, obtaining a significant reduction in the month of July with a total of 6 failures that gives 16% compared to the months of April with 10 failures that gives 27%, May with 9 failures that gives 24%, June with 12 failures that gives 32% of the total failures presented in these months.